2011
DOI: 10.1039/c0lc00228c
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput tracking of single yeast cells in a microfluidic imaging matrix

Abstract: Summary Time-lapse live cell imaging is a powerful tool for studying signaling network dynamics and complexity and is uniquely suited to single cell studies of response dynamics, noise, and heritable differences. Although conventional imaging formats have the temporal and spatial resolution needed for such studies, they do not provide the simultaneous advantages of cell tracking, experimental throughput, and precise chemical control. This is particularly problematic for systems-level studies using non-adherent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(62 citation statements)
references
References 55 publications
(104 reference statements)
0
59
0
Order By: Relevance
“…Microfluidic devices have been developed to capture yeast cells for high-resolution imaging analysis during vegetative growth (16)(17)(18)(19)(20). Recently, such devices have been designed that enable the tracking of yeast cells throughout their lifespan, making it possible to record and study cellular phenotypic changes during aging (21)(22)(23).…”
Section: Saccharomyces Cerevisiaementioning
confidence: 99%
“…Microfluidic devices have been developed to capture yeast cells for high-resolution imaging analysis during vegetative growth (16)(17)(18)(19)(20). Recently, such devices have been designed that enable the tracking of yeast cells throughout their lifespan, making it possible to record and study cellular phenotypic changes during aging (21)(22)(23).…”
Section: Saccharomyces Cerevisiaementioning
confidence: 99%
“…Improved designs for fundamental components include normally closed valves (NCVs) [16 ,17], structured valves [18], cell traps [19], and capacitors and diodes ( Figure 1a) [20,21]; higher-level components that have been introduced include a chamber array [22], a high performance separation column [23 ], a gradient selector (Figure 1b) [23 ], a long term gradient generator [24 ], a 2D spatial gradient controller [25], an agar filled chamber [26] and a mutilaminate mixer [27].…”
Section: Component-level Developmentsmentioning
confidence: 99%
“…For example, agar filled chambers for cell culturing [26] and high-performance separation columns for chromatography [23 ] require viscous liquids to fill in small microchambers. Such operations are realized using a series of valves that fill PDMS chambers with appropriate materials, and are (a) Picture of the 30-plex chip for long term gradient generation (top) and the description of flow-switching which provides the stable gradient under noflow condition (bottom), reproduced by permission [24].…”
Section: Component-level Developmentsmentioning
confidence: 99%
“…Recent studies have shown the great potential of microfluidic culture platforms in providing (i) complex internal or external cell microenvironments Mehling and Tay, 2014;Sanati, 2014), (ii) advantages of miniaturization for handling a small sample volume for detailed quantitative analysis of living cells (Mehling and Tay, 2014), and (iii) a platform for high-throughput analysis of cell behavior and continuous tracking of the changed behavior of cells against time-dependent external stimuli (Charvin et al, 2008;Falconnet et al, 2011;Huh et al, 2012;Lecault et al, 2011;Mehling and Tay, 2014;Sanati,2014;Vyawahare et al, 2010). The use of microfluidic devices in current trials is an initial step, but quantitative analysis of living systems using a 'labon-a-chip' device would offer great opportunities for advanced biological science and engineering.…”
Section: Introductionmentioning
confidence: 99%
“…A 'Lab-on-a-chip device,' manipulated by micro-electromechanical systems (MEMS) technology, is presently recognized as an emerging strategy for the design and manipulation of in vitro cell culture platforms to solve current limitations (Charvin et al, 2008;Falconnet et al, 2011;Huh et al, 2012;Lecault et al, 2011;Mehling and Tay, 2014;Sanati, 2014;Kim et al, 2014;Vyawahare et al, 2010). Recent studies have shown the great potential of microfluidic culture platforms in providing (i) complex internal or external cell microenvironments Mehling and Tay, 2014;Sanati, 2014), (ii) advantages of miniaturization for handling a small sample volume for detailed quantitative analysis of living cells (Mehling and Tay, 2014), and (iii) a platform for high-throughput analysis of cell behavior and continuous tracking of the changed behavior of cells against time-dependent external stimuli (Charvin et al, 2008;Falconnet et al, 2011;Huh et al, 2012;Lecault et al, 2011;Mehling and Tay, 2014;Sanati,2014;Vyawahare et al, 2010).…”
Section: Introductionmentioning
confidence: 99%